Medium-high mountain approach to avalanche risk. The Vosges Range as a case of study (France) - Giacona, Florie (2009)
Although avalanche risk is the deadliest natural risk in Alsace, winter of 1999-2000 suddenly brought up this underestimated, forgotten, or even denied danger. This interdisciplinary research emphasized more than 250 avalanche events, from the end of the 18th century until today. We reset these events into the context of climatic variation and evolution of land occupation. We also considered a typology and a scale for avalanche intensity, specifically regarding medium-high mountains. Eventually we will discuss the current state of avalanche risk.